2014
DOI: 10.1186/1472-6963-14-448
|View full text |Cite
|
Sign up to set email alerts
|

Development and impact of the Iranian hospital performance measurement program

Abstract: BackgroundIran developed a national hospital performance measurement program (HPMP) which has been implemented annually throughout its hospitals since 1997. However, little is known yet about its development and the impact of the program on hospital performance.This study aims to describe the development and process of implementation of the HPMP, and to explore the impact on hospital performance by looking at the trends of performance scores of all different types of Iranian hospitals.MethodsThis was a mixed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…A study in Lebanon showed that accreditation improved quality of health care, particularly in documentation and translating theories into actions [56]. Aghaei Hashjin et al reported an improvement in the performances of hospitals in Iran following implementation of a performance measuring program [57]. Moreover, auditing and monitoring coupled with education improved pain assessment and management in Canadian paediatric hospital [55].…”
Section: Discussionmentioning
confidence: 99%
“…A study in Lebanon showed that accreditation improved quality of health care, particularly in documentation and translating theories into actions [56]. Aghaei Hashjin et al reported an improvement in the performances of hospitals in Iran following implementation of a performance measuring program [57]. Moreover, auditing and monitoring coupled with education improved pain assessment and management in Canadian paediatric hospital [55].…”
Section: Discussionmentioning
confidence: 99%
“…Although hospitals make efforts regarding administrative processes in relation to the provision of services from admission to discharge to use specific strategies to accelerate the process, in practice, many of these processes are not optimal and are sometimes far from that expected. [182829] Some researchers reported patient satisfaction from the hospital general services to be at a lower level compared to the medical and nursing services. [30] A meta-analysis study regarding the satisfaction of patients toward hospital emergency centers in Iran showed that patients’ satisfaction scores ranged from 24 to 98.4 with an average of 68.9% and is somewhat acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…Two questionnaires were used in this study: To design quality supply chain questionnaire firstly, based primarily on studies that had been done in the field, the supply chain quality dimensions were identified (Stanley & Wisner, 2001;Ajam et al, 2013;Chu-Hua & Madu, 2001;Azar & Mohamadlu, 2010;Hashjin et al, 2014;Kuei & Madu, 2001;Schneller, 2000;Stank et al, 2005;Power, 2005;Chen et al, 2013) and then given to the specialists in this field to prove its validity. In order to measure patient satisfaction on received services, the designed Questionnaire in the Assessment of health reform system in the field of treatment in September 2014 was used (Ministry of Health and Medical Education, 2014) and according to the research goals, the items were adjusted, the study data were collected based on the Likert scale was arranged (5 options), and open questions.…”
Section: Methodsmentioning
confidence: 99%